Evaluation of Cross-Coupling Decoupling in Islanded Microgrid Control with Inductor Current Feed-Forward Technique - Olayanju, Sunday; Dahunsi, Folasade Mojisola; Ponnle, Akinlolu Adediran (Faculty of Engineering, Universitas Brawijaya, 2024)
To control the voltage source inverter in an islanded microgrid, the d-q reference frame is employed chiefly because of its ability to model inverter's dynamic models accurately. It allows the use of a simple proportional-integral controller for control purposes. However, its use is plagued with the cross-coupling terms introduced by the transformation into the d-q frame in the inner current and outside voltage control loops. This paper presents stepwise design and modelling of the inverter dynamics in the d-q reference frame. The systematic algebraic elimination method with inductor current feed-forward was employed for decoupling cross-coupling terms in the current and voltage loop controller design. The method's effectiveness was evaluated in the voltage and current control; overshoots and distortions resulting from load change were better mitigated. Simulation results were presented for evaluating the controller performance in cross coupling terms.